Persepsi Komunitas Suporter Manchester United Sumbawa Barat Terhadap Kampanye Dukungan LGBT Pada Cabang Olahraga Sepak Bola - Dani Pratama (Universitas Katolik Widya Karya Malang, 2023)
LGBT is increasingly intensifying its global promotion to indoctrinate the audience into being accepted within society. An example of the recent worldwide discussion is the LGBT campaign through the sport of football. Football is the most popular sport in the world, and any phenomenon in football always becomes a topic of discussion in the media. Based on the above issue, the objective of this research is to understand the perception of football fans towards the LGBT support campaign in football. The research subject in this study is the Manchester United Supporters Community in West Sumbawa. The method used is descriptive qualitative. Data collection was conducted through interviews, making the direct answers given by the informants the data source for this study. The research findings indicate that there are two perceptions among the research informants. The first perception is to reject the LGBT campaign in football, while the second perception does not consider the LGBT campaign in football as a problem. The perception of the Manchester United supporters community in West Sumbawa towards the LGBT campaign in football is based on internal and external factors that influence how they interpret and respond to the received stimulus. Internal factors include experience, needs, judgment, and individual expectations, while external factors include physical appearance and environmental situations.